Midwifery care standards for the first stage of labour - Z. Railoon; A. G. W. Nolte (AOSIS, 1995)
Changes in the social and political structures have brought about changing demands on the delivery of health care. The restructuring of health care under the banner of comprehensive health care has brought about a diversity of lifestyles, traditions, cultures, customs and language barriers which presently cannot be met in totality because of lack of knowledge and understanding of the above-mentioned aspects on the part of health professionals.